PROGRAM PENGUATAN ASPEK MANAJEMEN KEUANGAN PADA PANTI ASUHAN NURJANNAH BATAM - Wisnu Yuwono; Johny Budiman; Richie Marlon; Aprilia Chandrawati; Coral Aswanti; Henly Henly; Greceila Veronica Tanita; Welliam Ali; Hendrawan Hendrawan (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Internasional Batam, 2020)
This community service program aims to improve the financial management aspects of partners, especially in the field of funding, because in the era of the COVID-19 pandemic, which was marked by declining economic conditions and had a major impact on the Nurjannah Orphanage, where donations also decreased. The program carried out is by working, namely holding drawing activities and from the results of the orphanage children's drawings are published on Instagram, and interested people will make donations by buying these pictures. The results of the activities that have been carried out indicate a significant additional donation for operational funding at the Nurjannah Orphanage-Batam.